Comparing incidence of enterocolitis after laparoscopic and open low anterior resection for stage II/III rectal cancer. Issue 3 (1st April 2014) - Inomata, Masafumi; Kusano, Toru; Etoh, Tsuyoshi; Akagi, Tomonori; Shibata, Tomotaka; Ueda, Yoshitake; Tojigamori, Manabu; Shiroshita, Hidefumi; Noguchi, Tsuyoshi; Shiraishi, Norio; Kitano, Seigo
Abstract Introduction We recently observed an increased incidence of severe enterocolitis following laparoscopic low anterior resection (LAR) in some patients with stage II/III rectal cancer. This study aimed to examine the influence of laparoscopic LAR on postoperative enterocolitis compared with open LAR for Stage II/III rectal cancer. Methods From April 2002 to March 2012, we evaluated 65 patients with stage II/III cancer of the upper or lower rectum who underwent LAR. Among these, 27 patients underwent open LAR and 38 underwent laparoscopic LAR. First, we compared short‐term outcomes between the two groups. Next, we evaluated the incidence of postoperative enterocolitis in the laparoscopic LAR group. The clinicopathological factors were examined by univariate and odds ratio (OR) analysis. Results Univariate analysis revealed significant differences in the occupancy rate, tumor location, depth of tumor invasion, operative time, amount of intraoperative blood loss, and postoperative enterocolitis between the laparoscopic and open groups. Postoperative enterocolitis developed in 6 of 38 patients (15.8%) in the laparoscopic group and in no patient in the open group. The occurrence of postoperative enterocolitis was significantly associated with BMI (≥28 kg/m2), operative time, and wound infection in the laparoscopic LAR group (OR: 0.11, 95% confidence interval: 0.044–0.280, P < 0.05; OR: 1.40, 95% confidence interval: 1.068–1.835, P < 0.05; and OR: 15.0, 95% confidence interval, 1.752–128.310, P < 0.05, respectively). Conclusion Postoperative enterocolitis occurred more frequently after laparoscopic LAR than after open LAR in patients with stage II/III rectal cancer. Clinical management in the perioperative period of laparoscopic LAR is necessary to prevent postoperative enterocolitis in obese patients and those with a prolonged operative time.